Chronic exposure to cigarette smoke transiently worsens the disease course in a mouse model of pulmonary paracoccidioidomycosis - Buccheri, Renata (2022)
Paracoccidioidomycosis (PCM) may present as an acute/subacute clinical form, characterized by a progressive disease arising from the airborne initial infection, or, most often, as an asymptomatic or subclinical infection that may manifest later during an individual’s life, the chronic form. Epidemiological studies show the existence of a strong association between smoking and the development of the chronic form. Current evidence demonstrates that cigarette smoke (CS) has immunosuppressive properties that could be implicated in the increasing susceptibility to the chronic form of PCM. To address this issue, we developed a murine model of a non-progressive pulmonary form of PCM that was exposed to CS at a magnitude that mimicked a moderate smoker. The chronic CS exposure started after 2 weeks and lasted up until 20 weeks post-infection, with the aim of mimicking human natural history, since it is estimated that individuals from endemic areas are infected early in life. The control group consisted of infected but not CS-exposed mice. We assessed the lung fungal burden (colony forming units [CFU]) and the area affected by the granulomatous inflammatory response, fungal dissemination to spleen and liver, and, by immunohistochemistry, the presence of CD4 and CD8 lymphocytes, CD68 and MAC-2 macrophages, and IFN-γ, IL-10 and TNF expressing cells within the granulomatous response. We detected a CS effect as early as 2 weeks after exposure (four weeks post-infection) when the lung CFU of exposed animals was significantly higher than in their non-exposed counterparts. At 12 weeks, the CS-exposed animals presented a more severe disease, as witnessed by the persistent higher lung fungal load (although it did not reach statistical significance [ p = 0.054]), greater dissemination to other organs, greater affected area of the lung, decreased IFN-γ/IL-10 ratio, and higher TNF expression within the granulomas, compared with CS-non-exposed mice. The number of CD4 and CD8 lymphocytes infiltrating the granulomas was similar between both mice groups, but there was a decrease in the number of MAC-2+ macrophages. No difference was noted in the CD68+ macrophage number. However, the follow-up in week 20 showed that the immunological effects of exposure to CS ceased, with both CS and NCS mice showing the same infectious features, i.e., a trend for resolution of the infection. In conclusion, we show that chronic CS-exposure alters the course of the disease in an experimental model of subclinical pulmonary PCM, confirming the epidemiological link between CS-exposure and the chronic form of PCM. However, we also show that this effect is transitory, being detected between 4- and 12-weeks post-infection but not thereafter. The possible immune mechanisms that mediate this effect and the reasons for its transitory effect are discussed.